2014
DOI: 10.1159/000356991
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of 80-Watt KTP and 120-Watt HPS GreenLight Photoselective Vaporization of the Prostate

Abstract: Objective: Photoselective vaporization of the prostate (PVP) is becoming a surgical treatment alternative of transurethral resection of the prostate for male lower urinary tract symptoms (LUTS) secondary to benign prostatic obstruction (BPO). We evaluated the outcome and postoperative complications of PVP performed by 80-W KTP and 120-W HPS GreenLight lasers (AMS®) over a 4-year period. Materials and Methods: This is a prospective monocentric study that included all patients who underwent PVP. They had routine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
1
8
0
2
Order By: Relevance
“…In the current study, a 3.9-point increase was found at the end of the 3rd month and a 4.2-point increase at the end of the 12th month. Functional improvements following PUL were less than those previously reported for TURP and PVP (10-13 ml/s) during 12-month follow-ups [18,19,20,21]. In parallel with Qmax values, there was a significant increase in Qavg at the end of the 3rd and 12th months.…”
Section: Discussionmentioning
confidence: 57%
“…In the current study, a 3.9-point increase was found at the end of the 3rd month and a 4.2-point increase at the end of the 12th month. Functional improvements following PUL were less than those previously reported for TURP and PVP (10-13 ml/s) during 12-month follow-ups [18,19,20,21]. In parallel with Qmax values, there was a significant increase in Qavg at the end of the 3rd and 12th months.…”
Section: Discussionmentioning
confidence: 57%
“…Barber et al [9], using an 80 W laser, did not detect any absorption, while Hermanns et al [8],using a 120 W laser, found that 44% of 50 patients investigated showed absorption with a median of 725 ml. Long-term results of such treatments with green-light lasers of 80 W [25], 120 W [26] and 180 W [27] have been reported, but because of differing study designs, they are not comparable.…”
Section: Discussionmentioning
confidence: 99%
“…The results show a high success rate, as only 4 of 67 patients that were already fitted with a long-term catheter were discharged with a long-term catheter in place [18]. However, secondary TURP was required in 4.2% of patients.…”
Section: Discussionmentioning
confidence: 99%